Curriculum Models for the 21st Century
XXVI, 444 p.
Keywords: Changing student profiles and the increasing availability of mainstream and specialized learning technologies are stretching the traditional face-to-face models of teaching and learning in higher education. Institutions, too, are facing far-reaching systemic changes which are placing strains on existing resources and physical infrastructure and calling into question traditional ways of teaching through lectures and tutorials. And, with an ever-increasing scrutiny on teaching and teachers’ accountability for positive educational outcomes, the call for closer attention to learning, teaching and, most especially, to the design and delivery of the curriculum is given increasing relevance and importance. Research provides strong evidence of the potential for technologies to facilitate not only cognition and learning but also to become integral components in the redesign of current curriculum models. Some Universities and individual academics have moved along this pathway, developing new and innovative curriculum, blending pedagogies and technologies to suit their circumstances. Yet, there are others, unsure of the possibilities, the opportunities and constraints in these changing times. Curriculum Models for the 21st Century gives insights into how teaching and learning can be done differently. The focus is on a whole of curriculum approach, looking at theoretical models and examples of practice which capitalize on the potential of technologies to deliver variations and alternatives to the more traditional lecture-based model of University teaching.